Diversity and learning for innovation: Dialogue for collaboration - Rose-Anderssen, Christen; Allen, Peter M. (Emerald Group Publishing Limited, 2008)
This paper aims to develop an approach for improving linguistic skills to enhance work collaboration. Design/methodology/approach – A framework has been developed using principles of complex systems thinking, cultural-historical activity theory and theories of intercultural communication in an action research setting. Findings – Organisational development and change are never a straightforward task, which the case clearly demonstrates. These are tension-filled processes of continuously changing power relationships and distances between people. The development of shared sense making is an iterative learning process. Co-developing shared communication strategies enhances dialogue and collaboration. Research limitations/implications – A single and in practice unsuccessful case has been the basis of the research findings. Although saturation of data was therefore never reached, typical inhibiting factors were brought to the surface. Controversy and underlying inhibitions may not always be easy to detect in successful cases. The understanding from this unsuccessful case may therefore be helpful for further research. Practical implications – Collaboration and change in the workplace are complex processes and are therefore difficult to implement. Collective approaches for developing communication strategies are highly dependent on including all affected actors. Originality/value – The realisation of the complexity of organisational change processes is important. This creates an awareness of a need and responsibility for everyone affected to try and co-develop the practices for change. It is the bringing together of the diverse experiences into learning processes through dialogue that facilitates these changes. There must be an appreciation that the outcome is still unpredictable in a process of change. Collective ownership of the changes is essential for success.
Keywords: Complex activity networks; Exploration and learning; Dialogue and collaboration